QUALITY OF CARE FOR ACUTE SEVERE COLITIS. MUCH DONE, MORE TO DO. (8th June 2013) - Gibson, D J; Rafter, N; Keegan, D; Byrne, K; Martin, S; O'Connell, P R; Winter, D C; Hyland, J M; Mulcahy, H E; Cullen, G; Doherty, G A
Abstract : Introduction: Optimal management of in-patients with Ulcerative Colitis (UC) is important, as it is associated with morbidity and mortality. The national IBD audit in the UK has defined quality standards for the care of acute colitis. Aims/Background: To assess whether our management of patients with acute UC complies with suggested quality standards and identify areas for quality improvement. Method: This was a retrospective review of all patients admitted with a principle discharge diagnosis of UC in a tertiary referral centre between January 2010-November 2011. Patients admitted electively either for endoscopy or UC related surgery were excluded. Results: 91 patients were identified with a principal discharge diagnosis of UC; 39 patients were excluded (elective admission for surgery or endoscopy). 52 patients hospitalised with acute severe colitis were considered eligible for further study. M:F ratio=36:16. Median age was 47.0 (+/−17.68). Median length of stay was 8 days. 44 patients were admitted medically and 8 were admitted surgically. Stool sample for culture and sensitivity and C Difficile toxin was sent in 40 of 52 cases (76.9%). 40 patients (76.9%) underwent flexible sigmoidoscopy within 4 days of admission. 48 patients (92.3%) received steroids, of whom 72.9% were prescribed bone protection. VTE prophylaxis was prescribed in 46/52 (85.7%). 37/52 (53.8%) patients were assessed by a dietician during their admission. Medical teams were more likely to send stool samples (81% vs 50%) and prescribe bone protection for those on steroids (73% vs 38%), whereas rates of VTE prophylaxis prescription were comparable (89% vs 88%) between medical and surgical admissions. Conclusion: This study highlights good practice in the care of patients with acute severe colitis but identifies areas for quality improvement. All patients should have a stool sample sent at admission and should receive VTE prophylaxis. The use of an intergrated care pathway for patients with acute severe colitis may assist in ensuring quality standards are optimized.